2018
DOI: 10.3389/fimmu.2018.02047
|View full text |Cite|
|
Sign up to set email alerts
|

The Challenge of the Pathogenesis of Parkinson's Disease: Is Autoimmunity the Culprit?

Abstract: The role of autoimmunity in Parkinson's disease (PD), as one of the most popular research subjects, has been intensively investigated in recent years. Although the ultimate cause of PD is unknown, one major area of interest remains identifying new therapeutic targets and options for patients suffering from PD. Herein, we present a comprehensive review of the impacts of autoimmunity in neurodegenerative diseases, especially PD, and we have composed a logical argument to substantiate that autoimmunity is activel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 107 publications
1
33
0
1
Order By: Relevance
“…Recent clinical evidence shows that autoantibodies play roles in disease; therefore, the concept that neurodegenerative diseases may have an autoimmune etiology has been suggested [ 21 , 22 , 23 ]. Due to recent advances in technology related to antibody screening, many studies are attempting to identify autoantibodies associated with neurodegenerative diseases [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent clinical evidence shows that autoantibodies play roles in disease; therefore, the concept that neurodegenerative diseases may have an autoimmune etiology has been suggested [ 21 , 22 , 23 ]. Due to recent advances in technology related to antibody screening, many studies are attempting to identify autoantibodies associated with neurodegenerative diseases [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study found that Graves' disease may share genetic pathways with PD and is closely linked to PD's specific clinical manifestations (13). Amplified autoimmune reactions of Graves' disease via shared genetic pathways may also contribute to PD development (14). Third, hyperthyroidism triggers symptoms in patients with subclinical vulnerability to PD by acting on PD's biological substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson’s disease (PD) is an adult onset neurodegenerative disease characterized by selective degeneration of neurons, including loss of dopaminergic neurons and the presence of Lewy bodies containing α-synuclein, which results in motor and nonmotor symptoms [139,140,141]. α-synuclein plays a leading role in the initiation and progression of neurodegeneration as a result of neurotoxicity induction by various pathways, such as inflammation, oxidative stress as well as autophagy abnormalities [141,142]. TLR1 and TLR2 on microglia recognize α-synuclein followed by the activation of phagocytic TAM receptor tyrosine kinases: Axl and Mer [143].…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%